Identifikasi Endoparasit pada Kambing Kacang (Capra hircus) yang Dipelihara Secara Tradisional di Kecamatan Pulau Ternate - Gunawan Hatari; Sri Lestari; M Iksan B Aly (Universitas Khairun, 2026)
The Kacang goat (Capra hircus) is an indigenous Indonesian small ruminant predominantly raised under a traditional-extensive husbandry system in Pulau Ternate Subdistrict, Ternate City, North Maluku. This system, characterized by free-range grazing, inadequate environmental sanitation, and the absence of scheduled anthelmintic programs, is associated with elevated risk of gastrointestinal endoparasite infection that substantially reduces livestock productivity. This study aimed to identify endoparasite species, determine prevalence and infection intensity, and analyze the association of age, sex, and body condition score (BCS) with infection occurrence. A descriptive exploratory survey design was employed using purposive sampling of 50 Kacang goats from five sub-villages. Fecal samples were examined using native smear, saturated NaCl flotation, sedimentation, and quantitative McMaster Eggs Per Gram (EPG) methods. Nine endoparasite species were identified: Haemonchus sp. (54%), Trichostrongylus sp. (46%), Oesophagostomum sp. (40%), Strongyloides sp. (32%), Eimeria sp. (28%), Ostertagia sp. (24%), Moniezia sp. (18%), Trichuris sp. (14%), and Fasciola sp. (10%). Overall prevalence reached 78% with Nematoda as the dominant class and 79.49% mixed infections. Age showed a significant association (p=0.012); sex (p=0.217) and BCS (p=0.064) were not significant. The high prevalence underscores the urgent need for structured parasite control programs and husbandry education for farmers in Pulau Ternate Subdistrict.